Minimally invasive unilateral arytenoid lateralization in dogs: A cadaveric study. (October 2015) - Shipov, A.; Israeli, I.; Weiser, M.; Kelmer, E.; Klainbart, S.; Milgram, J.
Abstract: The aim of this study was to develop a minimally invasive thyroarytenoid lateralization technique (MITAL). Eleven unilateral MITAL procedures were performed on 11 canine cadavers. Two hypodermic needles were passed through the skin into the lumen of the larynx, penetrating the thyroid and arytenoid cartilages. Suture material was passed through the needles to lateralize the arytenoid cartilage. A rigid endoscope was used to visualize needle insertion and suture material placement. A key-hole approach to the larynx was performed and the suture material was knotted on the lateral aspect of the thyroid cartilage. The change in the rima glottidis area was recorded as were the duration of the procedure and complications encountered. The landmarks for needle insertion were easily palpated, and a significant increase in the area of the rima glottidis was documented after performing unilateral MITAL. In conclusion, unilateral MITAL is a quick, minimally invasive procedure which increases the area of the rima glottidis in cadaveric dogs. Highlights: A minimally invasive thyroarytenoid lateralization (MITAL) in canine cadavers is described. Suture material is inserted percutaneously through 2 needles, into the laryngeal lumen. A rigid endoscope is used to assess proper suture placement. Suture material is tied directly on the thyroid cartilage through a key-hole approach. A significant increase in rima-glottidis was demonstrated after tying the suture.